Direitos fundamentais trabalhistas: cognição da execução fiscal de multa por infração à legislação laboral à luz do valor do trabalho digno - Silva, Thiago Moreira da (2017)
This paper aims to discuss the role of human work valuation and labor fundamental rights to the conformation of the corporate activity and its repercussions for the resizing of cognition to be developed in the enforcement of fines imposed on labor laws violations under the theoretical post-positivism framework. In the first part of the work, through the theoreticaldescriptive method, it will expose the transformation of the legal thinking of positivism to the current generically named post-positivism, as well as the rise of human dignity to the center of the legal system and the role played by the social values of labor for the hermeneutical activity. In a second moment, also by the same method, it will evidence the connection of labor fundamental rights with the foundations of the Republic mentioned above and its insertion into the constitutional economic order, as objective order of values, through the enhancement of the human labor valuation, conditioning factor of constitutional freedoms to undertake and one of the company's social function parameters. Thus, it will expose the importance of regulating and inspecting labor relations in order to build an idea of Social Justice that promotes the dignified existence of all, inducing a model of economic development that is not founded solely on monetary or patrimonial bases, according to the thinking of Amartya Sen. In the last part of the work, through a rational argument and from the previous theoretical exposition, will be sustained the resizing of cognition of the enforcement of labor fines in function of the necessity of the adoption of hermeneutic methods compatible with substantive due process clause inspired by post-positivist canons, such as the theories of weighting of Alexy and the dialogue of sources of Erik Jayme, to confer appropriate treatment to the values adopted by the constitutional economic order and fundamental labor rights - in their objective dimension - which gravitate around these executive demands.